1999 BPI science awards - Ruiz, Conrado R., Jr. (Animo Repository, 1999)
Three Outstanding DLSU-Manila students were honored by the Bank of the Philippine Islands during the 1999 BPI Science Awards held during the University Week 1999. The awardees were Conrado R. Ruiz, Jr. of the Computer Science Edzel R. Lapira of the Electronics and Communications Engineering and Richard N. Marquez, also of the Electonics and Communications Engineering.